If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 11 + -6n Solving 8 = 11 + -6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '6n' to each side of the equation. 8 + 6n = 11 + -6n + 6n Combine like terms: -6n + 6n = 0 8 + 6n = 11 + 0 8 + 6n = 11 Add '-8' to each side of the equation. 8 + -8 + 6n = 11 + -8 Combine like terms: 8 + -8 = 0 0 + 6n = 11 + -8 6n = 11 + -8 Combine like terms: 11 + -8 = 3 6n = 3 Divide each side by '6'. n = 0.5 Simplifying n = 0.5
| T-7=b-(-7) | | 10y+4=-13 | | -3x-21=x+15 | | -2+3w=-8 | | k-14.4=-18.39 | | x-24=2x | | x-24=2s | | 2+x-2x=0 | | 3x+8y=438 | | 3x+86y=438 | | 2(2x+3)+9x-7=90 | | 3x+86y=4381 | | 3x-86y=4381 | | 6-(3b+1)=5(-2b-2) | | r+6.1=0.6 | | 6x+1=2z+1 | | .5k+4=12 | | x-y=2+2x+y+13 | | t+6+-9=-30 | | 2+3x+4x=72 | | x-5-2=-10 | | 77+11x=127+x | | x+17=7x+41 | | 2(p-4)=3(p+4) | | x-25=5x+7 | | X+X^2+X^3=6 | | 6x+4y=3x+8y | | X^2+3x+9=17 | | 7x-124=9 | | x^4-6x^3+5x-5=0 | | 3x-13=-20 | | 6x-22=2x+6 |